Theological Perspective of The Biblical Text of The Flood In Gen 6,1-9,17: The Novelty of the Biblical Message in the Material of The Flood - Gómez Alarcón, Stalin (2019)
The author elaborates an exegetical-hermeneutical study, using the historical-critical method, of the story of the universal flood at Genesis 6,1-9,17. This is an elaboration of the yavista (J) and priestly (P) traditions. The yavista presents Noah as the righteous man in the midst of human evil; the priestly presents him as the new Adam, in the midst of the infidelity of the chosen people. The flood represents a return to the initial chaos; the salvation of Noah and his family, a return to the salvific project of God. The story presents us with a biblical anthropology, which recognizes the presence of evil in the human heart, but highlights the fidelity, kindness and obedience of Noah, for which God grants a new salvation.